Remote Detection of the Electric Field Change Induced at the Seismic Wave Front from the Start of Fault Rupturing - Yukio Fujinawa; Kozo Takahashi; Yoichi Noda; Hiroshi Iitaka; Shinobu Yazaki (International Journal of Geophysics)
Seismic waves are generally observed through the measurement of undulating elastic ground motion. We report the remote detection of the Earth's electric field variations almost simultaneously with the start of fault rupturing at about 100 km from the fault region using a special electric measurement. The rare but repeated detection indicates that the phenomenon is real. The characteristic time of diffusion is almost instantaneous, that is, less than 1 second to travel 100 km, more than ten times faster than ordinary seismic P wave propagation. We suggest that the measured electric field changes are produced by the electrokinetic effect through increased pore water pressure of the seismic pulse. It is also suggested that the long range propagation is due to the surface wave mode confined near the interface of the different conductivity. The length scale of the finite strength of the electric field is 16 km, 160 km for electric conductivity of 0.01, 0.001, Sm−1, respectively. This phenomenon suggests a new seismic sensing method and a new earthquake early warning system providing more seconds of lead time.